PERANAN INFRASTRUKTUR TEKNOLOGI INFORMASI BAGI PERKEMBANGAN USAHA KECIL DAN MENENGAH DI INDONESIA - Widajanti, Erni (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Environmental, organizational and technological factors create a high competitive business environment, where these factors are rapidly changing, which is sometimes unpredictable way. Due to this rapid change, the company (in this case SMEs) need to react quickly in the face of problems and opportunities resulting from the new business environment (which focuses on the consumer). So in order to succeed (survive) in this dynamic world, companies should not only perform traditional measures such as lowering costs, but also perform activities such as changing the structure of innovation or process as a critical responses activities. Most response activities can be facilitated by better information technology. Keywords: small and medium enterprises, information technology, lowering cost, critical responses activities